Cardiotoxicity of immune checkpoint inhibitors: A systematic review and meta-analysis of randomised clinical trials. (May 2021) - Agostinetto, Elisa; Eiger, Daniel; Lambertini, Matteo; Ceppi, Marcello; Bruzzone, Marco; Pondé, Noam; Plummer, Chris; Awada, Ahmad H.; Santoro, Armando; Piccart-Gebhart, Martine; de Azambuja, Evandro
Abstract: Background: Immune checkpoint inhibitors (ICIs) may cause potentially life-threatening adverse events (AEs), but the risk of cardiotoxicity has not been fully investigated. It is also unknown whether ICI combinations increase cardiotoxicity compared with single ICI. We aimed to assess the cardiotoxicity of ICI in a range of tumour types. Methods: This systematic review and meta-analysis was conducted according to PRISMA guidelines (PROSPERO registration number: CRD42020183524). A systematic search of PubMed, MEDLINE, Embase databases, and conference proceedings was performed up to 30 June 2020. All randomised clinical trials comparing ICI with other treatments (primary objective) or dual-agent ICI versus single-agent ICI (secondary objective) in any solid tumour were included. Pooled risk ratios (RRs) with 95% confidence intervals (95% CIs) for cardiotoxicity events were calculated using random effect models. Results: Eighty studies including 35, 337 patients were included in the analysis (66 studies with 34, 664 patients for the primary endpoint and 14 studies with 673 patients for the secondary endpoint). No significant differences in terms of cardiac AEs were observed between ICI and non-ICI groups (RR 1.14, 95% CI 0.88–1.48, p = 0.326) nor between dual ICI and single ICI groups (RR 1.91, 95% CI 0.52–7.01, p = 0.329). Myocarditis incidence did not significantly differ between ICI and non-ICI groups (RR 1.11, 95% CI 0.64–1.92, p = 0.701) nor between dual ICI and single ICI groups (RR 1.10, 95% CI 0.31–3.87, p = 0.881). No differences were observed in subgroup analyses according to tumour type, setting of disease, treatment line, and type of treatment. Conclusion: The use of ICI as single or combination regimens is not associated with increased risk of cardiotoxicity. Highlights: Immune checkpoint inhibitors (ICIs) may cause life-threatening adverse events (AEs). The risk of cardiotoxicity of ICIs has been poorly investigated. In our meta-analysis, ICIs were not associated with increased cardiotoxicity risk. Cardiac AEs in clinical trials should be reported as completely as possible.